What is the solution to the system of equations below? y = negative one-third x + 6 and x = –6 (–6, 8) (–6, 4) (8, –6) (4, –6)

Answers

Answer 1
Answer: It’s (-6,8) because you substitute x for -6, and solve. So 1/3 times -6+-6= 8. —> x=8
Answer 2
Answer:

Answer:(-6,8)

Step-by-step explanation:


Related Questions

3 times x minus 2/5 =8/5 what is x equal to
The length of the base of a right triangle is 32 centimeters, and the height is 10 centimeters. What is the area of the triangle?A) 42 square centimeters B) 74 square centimeters C) 160 square centimeters D) 320 square centimetersI would like some help on this please! If someone could explain how to do this, it would be awesome! Thank you!
What is the greatest common factor of 16 and 64
What is the decimal for 17 40
Arnie's car used 100 cups of gasoline during a drive.He paid $3.12 per gallon of gas.How much did the gas cost?

If Colorado Springs, Colorado, has 1.4 times more days of sunshine than Boston, Massachusetts, how many days of sunshine does each city have if there are a total of 475 days of sunshine between the two in a year?

Answers

Suppose, number of sunshine days in Boston, Massachusetts is: x

Then, number of sunshine days in Colorado Spring, Colorado will be: 1.4 x

Given that, total number of days of sunshine for both city is: 475

That is, x+1.4x = 475

Solving for x,

x=198

1.4x= 277

Therefore,

Number of sunshine days in Boston, Massachusetts is 198

and

Number of sunshine days in Colorado Spring, Colorado is 277

What property describes the number sentence

Answers

Additive Identity Property

1. Simplify: a^7/a^4A. 1/a^3
B. a^3
C. -a/a^2
D.a^4/a^3

2. Simplify: r^2s^4t/r^2st^3
A. s^3/t^2
B. s^3/t
C. s^2t^3
D. s/t

3. Simplify: 3x^6/18x
A. 1/6
B. x^4/6
C. x^5/6
D. x^6/6

4. Identify the property demonstrated 4^3x4^7 = 4^3+7
A. Quotient of Powers Property
B. Power of a Power Property
C.Power of a Product Property
D.Product of Powers Property

5. Identify the property demonstrated: (a^7)^3 = a^7 x 3
A. Power of a Product Property
B. Quotient of Powers Property
C. Product of Powers Property
D. Power of a Power Property


Thank you so much whoever helps!!!

Answers

1)a^7/a^4
=a^[7-4]
=a³


2) r²s⁴t/r²st³
=s⁴-¹.t¹-³
=s³.t-²
=s³/t²

3)3x^6/18x
=x^5/6





Please help! Its for my big test tomorrow!

Answers

Answer:

# The solution x = -5

# The solution is x = 1

# The solution is x = 6.4

# The solution is x = 4

# The solution is 1.7427

# The solution is 0.190757

Step-by-step explanation:

* Lets revise some rules of the exponents and the logarithmic equation

# Exponent rules:

1- b^m  ×  b^n  =  b^(m + n) ⇒ in multiplication if they have same base

  we add  the power

2- b^m  ÷  b^n =  b^(m – n) ⇒  in division if they have same base we

   subtract  the power

3- (b^m)^n = b^(mn) ⇒ if we have power over power we multiply

   them

4- a^m × b^m = (ab)^m ⇒ if we multiply different bases with same  

   power then we multiply them ad put over the answer the power

5- b^(-m) = 1/(b^m)  (for all nonzero real numbers b) ⇒ If we have

   negative power we reciprocal the base to get positive power

6- If  a^m  =  a^n  ,  then  m  =  n ⇒ equal bases get equal powers

7- If  a^m  =  b^m  ,  then  a  =  b    or    m  =  0

# Logarithmic rules:

1- log_(a)b=n-----a^(n)=b

2- loga_(1)=0---log_(a)a=1---ln(e)=1

3- log_(a)q+log_(a)p=log_(a)qp

4- log_(a)q-log_(a)p=log_(a)(q)/(p)

5- log_(a)q^(n)=nlog_(a)q

* Now lets solve the problems

# 3^(x+1)=9^(x+3)

- Change the base 9 to 3²

9^(x+3)=3^(2(x+3))=3^(2x+6)

3^(x+1)=3^(2x+6)

- Same bases have equal powers

∴ x + 1 = 2x + 6 ⇒ subtract x and 6 from both sides

∴ 1 - 6 = 2x - x

∴ -5 = x

* The solution x = -5

# ㏒(9x - 2) = ㏒(4x + 3)

- If ㏒(a) = ㏒(b), then a = b

∴ 9x - 2 = 4x + 3 ⇒ subtract 4x from both sides and add 2 to both sides

∴ 5x = 5 ⇒ divide both sides by 5

∴ x = 1

* The solution is x = 1

# log_(6)(5x+4)=2

- Use the 1st rule in the logarithmic equation

∴ 6² = 5x + 4

∴ 36 = 5x + 4 ⇒ subtract 4 from both sides

∴ 32 = 5x ⇒ divide both sides by 5

∴ 6.4 = x

* The solution is x = 6.4

# log_(2)x+log_(2)(x-3)=2

- Use the rule 3 in the logarithmic equation

log_(2)x(x-3)=2

- Use the 1st rule in the logarithmic equation

∴ 2² = x(x - 3) ⇒ simplify

∴ 4 = x² - 3x ⇒ subtract 4 from both sides

∴ x² - 3x - 4 = 0 ⇒ factorize it into two brackets

∴ (x - 4)(x + 1) = 0 ⇒ equate each bract by 0

∴ x - 4 = 0 ⇒ add 4 to both sides

∴ x = 4

OR

∵ x + 1 = 0 ⇒ subtract 1 from both sides

∴ x = -1

- We will reject this answer because when we substitute the value

 of x in the given equation we will find log_(2)(-1) and this

 value is undefined, there is no logarithm for negative number

* The solution is x = 4

# log_(4)11.2=x

- You can use the calculator directly to find x

∴ x = 1.7427

* The solution is 1.7427

# 2e^(8x)=9.2 ⇒ divide the both sides by 2

e^(8x)=4.6

- Insert ln for both sides

lne^(8x)=ln(4.6)

- Use the rule ln(e^(n))=nln(e) ⇒ ln(e) = 1

∴ 8x = ln(4.6) ⇒ divide both sides by 8

∴ x = ln(4.6)/8 = 0.190757

* The solution is 0.190757

QUESTION 1

{3}^(x + 1)  =  {9}^(x + 3)

This is the same as:

{3}^(x + 1)  =  {3}^(2(x + 3))

Equate the exponents.

x+1=2(x+3)

Expand:

x+1=2x+6

Group similar terms;

2x-x=1-6

x=-5

QUESTION 2

log(9x - 2)  =  log(4x + 3)

Equate the arguments.

9x-2=4x+3

Group similar terms;

9x-4x=3+2

5x=5

Divide through by 5

x=1

QUESTION 3

log_(6)(5x + 4)  = 2

Take antilogarithm to obtain,

5x + 4 =  {6}^(2)

This implies that,

5x+4=36

5x=36-4

5x=32

x=32/5

or

x = 6 (2)/(5)

QUESTION 4

log_(2)(x)  +  log_(2)(x - 3)  = 2

Use the product rule of logarithms:

log_(2)x(x - 3)  = 2

Take antilogarithm,

{x}^(2)  - 3x =  {2}^(2)

{x}^(2)  - 3x - 4 = 0

Factor:

(x + 1)(x - 4) = 0

This implies that,

x =  - 1 \: or \: x = 4

But the domain is x>0, therefore the solution is

x=4

QUESTION 5

x=\log_(4)(11.2)

x=\log_(4)((56)/(5))

x=\log_(4)(56)-\log_(4)(5)

x=1.7 to the nearest tenth.

QUESTION 6

2e^(8x)=9.2

Divide both sides by 2.

e^(8x)=4.6

Take natural log of both sides

{8x}=\ln(4.6)

{x}=\ln(4.6)/ 8

x=0.2 to the nearest tenth.

Round 123 to the nearest ten

Answers

120 it is 120 it is 120

  
123 rounded to the nearest ten is 120

Solve for x. x2 + 7x + 10 = 0

Answers

the answer is negative 80 or like this -80